Pengaruh Edukasi Media Leaflet Terhadap Pengetahuan dan Sikap Remaja Putri Tentang Vaksin HPV - Andriyanti, Novia; Musniati, Nia (Media Literasi Indonesia, 2026)
Cervical cancer is one of the leading causes of death among women worldwide, with 99% of cases caused by the Human Papilloma Virus (HPV). It also remains a major cause of morbidity and mortality among women in Indonesia. Preventive efforts can be carried out through HPV vaccination. This study aimed to determine the effect of educational leaflets on the knowledge and attitudes of adolescent girls regarding the HPV vaccine. A quantitative method was applied using a Pre-Experimental One-Group Pretest-Posttest design. The sampling technique used was quota sampling, involving 33 female students from grades XI and XII at Budhi Warman 1 Senior High School, Jakarta. Data were analyzed using the Wilcoxon test and the Paired Sample T-Test. The results showed a significant increase after the distribution of the leaflet (p-value = 0.000), while there was no significant change in the respondents’ attitudes toward the HPV vaccine (p-value = 0.889). Education through leaflet media effectively improved adolescent girls’ knowledge about the HPV vaccine but did not significantly influence their attitudes. Promoting HPV vaccination in schools plays an important role in increasing adolescent awareness and encouraging preventive behavior, which is expected to reduce the incidence of cervical cancer through higher vaccination coverage.